1994
DOI: 10.1091/mbc.5.4.413
|View full text |Cite
|
Sign up to set email alerts
|

Direct interaction of v-Src with the focal adhesion kinase mediated by the Src SH2 domain.

Abstract: The recently described focal adhesion kinase (FAK) has been implicated in signal transduction pathways initiated by cell adhesion receptor integrins and by neuropeptide growth factors. To examine the mechanisms by which FAK relays signals from the membrane to the cell interior, we carried out a series of experiments to detect potential FAK interactions with proteins containing Src homology 2 (SH2) domains that are important intracellular signaling molecules. Using v-Src-transformed NIH3T3 cells, we showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
241
2
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(252 citation statements)
references
References 51 publications
8
241
2
1
Order By: Relevance
“…It is thus possible that integrin activation contributes to modulation of Src signaling, in FGF-2 induced tube formation. Fibronectin induced activation of FAK and subsequent binding of Src to phosphorylated Tyr397 in FAK is a well established integrinmediated signaling event (Schaller et al, 1994;Xing et al, 1994). Since Src activity is indispensable for IBEC di erentiation, it is interesting to note that FGF-2 has a potentiating e ect on Src ± FAK complex-formation in the collagen-cultured IBEC, which occurs in spite of the modest level of tyrosine phosphorylated FAK in these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus possible that integrin activation contributes to modulation of Src signaling, in FGF-2 induced tube formation. Fibronectin induced activation of FAK and subsequent binding of Src to phosphorylated Tyr397 in FAK is a well established integrinmediated signaling event (Schaller et al, 1994;Xing et al, 1994). Since Src activity is indispensable for IBEC di erentiation, it is interesting to note that FGF-2 has a potentiating e ect on Src ± FAK complex-formation in the collagen-cultured IBEC, which occurs in spite of the modest level of tyrosine phosphorylated FAK in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…The nonreceptor tyrosine kinase FAK contains a central kinase domain which is¯anked by N-and C-terminal domains lacking SH2 and SH3 domains. Several studies have shown direct binding of Src SH2 domain to the major autophosphorylation site of FAK (Schaller et al, 1994;Xing et al, 1994). This interaction is thought to occur in subcellular compartments called focal adhesions, where the cell contacts and binds to the extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid sequence of this site, YAEI, is close to the Src family SH2 consensus binding motif, and phosphorylation of the tyrosine creates a high-affinity binding site for the Src SH2 domain (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that autophosphorylation of FAK on a particular tyrosine residue, Y397, is an early, essential step for the full activation of FAK in response to many extracellular stimuli. The Y397 is the major site of FAK autophosphorylation, which creates a high affinity binding site for the Src-homology 2 domain of several proteins including the Src family kinases (Cobb et al, 1994;Schaller et al, 1994;Xing et al, 1994;Eide et al, 1995). Activated Src phosphorylates FAK on multiple sites, including Y576 and Y577, both of which are located in the activation loop within the kinase domain (Calalb et al, 1995;Lietha et al, 2007).…”
Section: Introductionmentioning
confidence: 99%